APLIKASI SISTEM PENGENDALI ENERGI LISTRIK MENGGUNAKAN RASPBERRYPI PADA SMART BUILDING - Masnur, Masnur (Jurnal Sintaks Logika, 2021)
Electrical energy is a very important requirement that must be met for human needs. The savings in electricity use have an impact on the preservation of nature apart from the usage costs incurred. Waste of electricity usage usually occurs due to negligence of users such as not turning off electrical equipment or forgetting to leave the room. Then the system "Electric Energy Control Application Using the Raspberry Pi on SmartBulding" was created. The method used is a system that can and can be controlled remotely using the internet, the system can be controlled either using a PC computer or using a mobile phone. The system uses the IP address contained in the raspberry pi, can control the system so that users don't have to worry too much when leaving the room, can monitor the temperature and see pictures of the room when left. By using this system users can control electrical equipment, can monitor room temperature when left away, can ON / OFF lights and air conditioners, monitor the movement of human objects which are then synchronized with the ON / OFF lights. The system is also capable of recording a room which is then saved in JPG format.